Manganese zinc ferrite magnetic core and preparation method thereof

By using the use of iron hydroxide and double eight -eight alkyl -based cycloidononononium manganese -zinc and iron oxygen magnetic cores, the problems of losses and BS characteristics of traditional materials in high frequency and large current conditions have been solved. The effect of BS value and low loss.

CN119371196APending Publication Date: 2025-01-28HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310932504.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Traditional MnZn ferrite materials have increased losses during high frequency use, and insufficient Bs characteristics, which cannot meet the application needs of high frequency and high currents.

Method used

The iron hydroxide is used as an iron source, and a double eight -eight alkyl dilately ammonium chloride additive is added to prepare manganese zinc iron oxygen cores through pre -fever, grinding, granular and sintering and other steps.

Benefits of technology

The BS value of the material is increased, and the loss is reduced at the same time. The 25 ° C BS can reach 544 or more, the 100 ° C BS can reach 441 or more, the 25 ° C PCV can reach 77, and the 100 ° C PCV can reach 120.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004362095100000081
    Figure BDA0004362095100000081
  • Figure BDA0004362095100000091
    Figure BDA0004362095100000091
Patent Text Reader

Abstract

The invention provides a manganese zinc ferrite magnetic core and a preparation method thereof, and the preparation method comprises the following steps: (1) mixing Fe (OH) 3, MnO and ZnO, and pre-sintering to obtain a pre-sintered material; (2) grinding the pre-sintered material, and adding an auxiliary material and a dioctadecyl dimethyl ammonium chloride additive to obtain a mixed material; (3) granulating the mixed material, and pressing to obtain a blank; and (4) sintering the blank to obtain the manganese-zinc ferrite magnetic core. Ferric hydroxide is used as an iron source, and a dioctadecyl dimethyl ammonium chloride additive is added to prepare manganese-zinc ferrite, so that the Bs of the material can be improved, and meanwhile, the loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnetic materials and relates to a manganese-zinc ferrite core and a preparation method thereof. Background Art

[0002] As the basic material of contemporary electronic industry and information industry, MnZn ferrite material is widely used in the fields of electronics and communications. As electronic components develop towards humanization, miniaturization and high output power, the use frequency of MnZn ferrite cores gradually moves from low frequency to high frequency, and the use conditions develop from small current to large current.

[0003] When the operating frequency moves toward high frequency, the loss of traditional MnZn ferrite will increase sharply and cannot meet the usage requirements, and the high-frequency loss needs to be reduced; when the usage conditions develop from small current to large current, the Bs characteristics of MnZn ferrite materials need to be higher.

[0004] CN113582238A discloses a method for preparing an iron source for manganese-zinc ferrite, wherein the titanium dioxide byproduct ferrous sulfate is impurized to obtain a pure ferrous sulfate solution, a certain amount of defoamer such as an alcohol defoamer or a polyether defoamer is added to the system comprising the pure ferrous sulfate solution, and then an ammonium bicarbonate solution or particles are added, and the reactant is filtered and washed after a certain reaction time to obtain a ferrous carbonate precursor and a filtrate, wherein the filtrate can be flashed to obtain agricultural grade ammonium sulfate powder, and the ferrous carbonate precursor is dried in an air atmosphere, and the manganese-zinc ferrite iron source can be obtained by drying for a certain period of time, and the titanium dioxide byproduct ferrous sulfate is used to remove impurities to obtain a pure ferrous sulfate solution, and the ferrous carbonate precursor is prepared and decomposed to obtain a manganese-zinc ferrite iron source, wherein the main component is ferric hydroxide. The defoamer and ammonium carbonate used by it can introduce impurities, and the purity of the iron source cannot be guaranteed.

[0005] CN113072370A discloses a manganese-zinc ferrite core and a preparation method thereof. In the preparation process of the core, one or a mixture of acrylic resin emulsion, polyvinyl alcohol, polyether, n-butanol, and ammonium citrate is added as a surfactant. The surfactant is basically completely decomposed in air at 600°C and has basically no effect on the magnetic densification reaction.

[0006] The manganese-zinc ferrite prepared by the above scheme has a low Bs and a high loss, which limits its application in practice. Therefore, it is of great theoretical and practical significance to develop a high-frequency manganese-zinc ferrite material with high Bs and low loss and a preparation method. Summary of the invention

[0007] The object of the present invention is to provide a manganese-zinc ferrite core and a preparation method thereof. The present invention uses ferric hydroxide as an iron source and adds dioctadecyl dimethyl ammonium chloride as an additive to prepare manganese-zinc ferrite, thereby improving the Bs of the material and reducing the loss.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a manganese-zinc ferrite core, the preparation method comprising the following steps:

[0010] (1) Fe(OH)3, MnO and ZnO are mixed and pre-sintered to obtain a pre-sintered material;

[0011] (2) grinding the pre-sintered material, adding auxiliary materials and dioctadecyl dimethyl ammonium chloride additive to obtain a mixed material;

[0012] (3) granulating the mixed material and pressing it to obtain a blank;

[0013] (4) Sintering the blank to obtain the manganese-zinc ferrite core.

[0014] The present invention uses Fe(OH)3 instead of traditional Fe2O3, which can improve the uniformity of raw material dispersion and the overall reaction activity of the powder. Dioctadecyl dimethyl ammonium chloride is added, and dioctadecyl dimethyl ammonium chloride can play the role of a surfactant due to the presence of a hydrophilic group and a hydrophobic group. On the other hand, dioctadecyl dimethyl ammonium chloride will promote the densification reaction of manganese-zinc ferrite and improve the density of manganese-zinc ferrite.

[0015] Preferably, the Fe(OH)3 in step (1) is prepared by the following method:

[0016] Oxygen is introduced into the ferrous salt solution to adjust the pH value to 3-4, and then polyacrylamide flocculant is added. After filtering, oxygen is continued to be introduced into the solution to adjust the pH value to 5-6, and then polyacrylamide flocculant is added. After centrifugation, filtering, washing and drying, the Fe(OH)3 is obtained.

[0017] The ferric hydroxide prepared by the method of the invention has high purity, small particle size and better activity.

[0018] Preferably, the ferrous salt comprises ferrous chloride.

[0019] Preferably, the mass concentration of the polyacrylamide flocculant is 0.8-1.5%, for example, 0.8%, 0.9%, 1%, 1.2% or 1.5%.

[0020] Preferably, the volume of the polyacrylamide flocculant added each time is 2 to 3 mL, for example, 2 mL, 2.2 mL, 2.5 mL, 2.8 mL or 3 mL.

[0021] Preferably, the drying temperature is 100-120°C, for example, 100°C, 105°C, 110°C, 115°C or 120°C.

[0022] Preferably, the drying time is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0023] Preferably, the molar ratio of Fe(OH)3, MnO and ZnO in step (1) is (70.1-70.5):(25.1-25.5):(4-4.9), for example: 70.1:25.3:4.6, 70.2:25.3:4.5, 70.4:25.1:4.5, 70.5:25.2:4.3 or 70.5:25.5:4, etc.

[0024] Preferably, the mixing method comprises ball milling.

[0025] Preferably, the ball milling time is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0026] Preferably, the temperature of the pre-sintering treatment in step (1) is 700-800°C, for example, 700°C, 720°C, 750°C, 780°C or 800°C.

[0027] Preferably, the pre-burning treatment time is 2 to 4 hours, for example: 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0028] Preferably, the atmosphere of the pre-firing treatment includes air.

[0029] Preferably, the pre-sintering treatment is followed by ball milling treatment.

[0030] Preferably, X50 of the pre-sintered material is 0.7-0.8 μm, for example, 0.7 μm, 0.72 μm, 0.75 μm, 0.78 μm or 0.8 μm.

[0031] Preferably, the auxiliary materials in step (2) include Co2O3, CaCO3, Nb2O5, ZrO2 and V2O5.

[0032] Preferably, based on the total mass of the Fe(OH)3, MnO and ZnO being 100%, the mass of the Co2O3 is 0.2-0.3%, for example: 0.2%, 0.22%, 0.25%, 0.28% or 0.3%, etc.

[0033] Preferably, the mass of CaCO3 is 0.08-0.12%, for example: 0.08%, 0.09%, 0.1%, 0.11% or 0.12%, etc.

[0034] Preferably, the mass of Nb2O5 is 0.01-0.05%, for example, 0.01%, 0.02%, 0.03%, 0.04% or 0.05%.

[0035] Preferably, the mass of ZrO2 is 0.01-0.05%, for example, 0.01%, 0.02%, 0.03%, 0.04% or 0.05%.

[0036] Preferably, the mass of the V2O5 is 0.01-0.03%, for example, 0.01%, 0.015%, 0.02%, 0.025% or 0.03%.

[0037] Preferably, based on the total mass of Fe(OH)3, MnO and ZnO as 100%, the mass of the dioctadecyl dimethyl ammonium chloride additive is 0.14-0.18%, for example: 0.14%, 0.15%, 0.16%, 0.17% or 0.18%, etc.

[0038] The dioctadecyl dimethyl ammonium chloride additive of the present invention undergoes three decomposition processes during the subsequent temperature-raising sintering process: in the first stage, a dehydration process occurs at 100°C; in the second stage, a decomposition process occurs at 150-200°C to produce hydrogen chloride; in the third stage, after 200°C, a hydrocarbon chain gradually decomposes. The densification reaction temperature of manganese-zinc ferrite is generally between 600-1000°C. After 600°C, 10% of the hydrocarbon chains of dioctadecyl dimethyl ammonium chloride remain. The residual hydrocarbon chains will act as flux and reducing agent to promote the densification reaction of manganese-zinc ferrite and improve the sintering density of manganese-zinc ferrite. Conventional organic surfactants such as polycarboxylic acid and other surfactants will hardly have hydrocarbon chains after 600°C and will not play a role in promoting the densification reaction of manganese-zinc ferrite.

[0039] Preferably, the granulation process in step (3) is preceded by a sieving process.

[0040] Preferably, the mesh number of the sieving screen is 50-80 meshes, for example: 50 mesh, 60 mesh, 70 mesh or 80 mesh.

[0041] Preferably, the granulation process comprises mixing the mixed material with a 10% polyvinyl alcohol solution for granulation.

[0042] Preferably, the temperature of the sintering treatment in step (4) is 900-1000°C, for example, 900°C, 920°C, 950°C, 980°C or 1000°C.

[0043] Preferably, the sintering treatment time is 6 to 8 hours, for example: 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours.

[0044] Preferably, the sintering process is performed according to a sintering curve of a balanced oxygen partial pressure atmosphere.

[0045] In a second aspect, the present invention provides a manganese-zinc ferrite core, which is manufactured by the method described in the first aspect.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] (1) The present invention uses ferric hydroxide as an iron source and adds dioctadecyl dimethyl ammonium chloride as an additive to prepare manganese zinc ferrite, which can improve the Bs of the material and reduce the loss.

[0048] (2) The method of the present invention can produce a manganese-zinc ferrite core with a 25°C Bs of more than 544, a 100°C Bs of more than 441, a 25°C Pcv of less than 77, and a 100°C Pcv of less than 120. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0050] The ferric hydroxide described in the present invention is prepared by the following method:

[0051] FeCl2 particles with a purity of 99.99% are prepared into a 140 g / L FeCl2 solution using deionized water. Oxygen is introduced into the FeCl2 solution until the pH value of the solution reaches 4. 3 ml of 1 wt% polyacrylamide flocculant is added, and impurities are removed by centrifugation. Oxygen is continued to be introduced into the FeCl2 solution until the pH value of the solution reaches 6. 3 ml of 1 wt% polyacrylamide flocculant is added, and centrifugation is performed. The solution is washed and the filtered Fe(OH)3 solid is baked at 100°C for 3 h to obtain Fe(OH)3.

[0052] Example 1

[0053] This embodiment provides a manganese-zinc ferrite core, and the preparation method of the manganese-zinc ferrite core is as follows:

[0054] (1) According to the main components Fe(OH)3, ZnO and MnO, 70.1 mol% of Fe(OH)3, 25.1 mol% of MnO and 4.8 ol% of ZnO were weighed, and the auxiliary materials were Co2O3: 0.2wt%, CaCO3: 0.08wt%, Nb2O5: 0.015wt%, ZrO2: 0.01wt%, V2O5: 0.01wt% and 0.14wt% of dioctadecyl dimethyl ammonium chloride according to the mass of the main components. Fe(OH)3, ZnO and MnO were mixed in a ball mill for 3 hours and then dried, and pre-calcined in an air atmosphere at 750°C for 3 hours to obtain a pre-calcined material;

[0055] (2) The pre-sintered material is subjected to secondary crushing using a ball mill, the crushing time is 3 hours, X50 is 0.7 μm, and Co2O3, CaCO3, Nb2O5, V2O5, ZrO2, and dioctadecyl dimethyl ammonium chloride additives are added in the required proportions to obtain a mixed material;

[0056] (3) After the dried mixture is passed through a 60-mesh sieve, 10% PVA is added to granulate the mixture, sieved to remove uneven particles, and pressed into a sample ring blank;

[0057] (4) The sample ring blank is placed in a sintering curve with a sintering temperature between 950° C. and a balanced oxygen partial pressure atmosphere, and is sintered for 7 hours to obtain the manganese-zinc ferrite core.

[0058] Example 2

[0059] This embodiment provides a manganese-zinc ferrite core, and the preparation method of the manganese-zinc ferrite core is as follows:

[0060] (1) According to the main components Fe(OH)3, ZnO and MnO, 70.5 mol% of Fe(OH)3, 25.5 mol% of MnO and 4 mol% of ZnO were weighed, and the auxiliary materials were Co2O3: 0.2wt%, CaCO3: 0.08wt%, Nb2O5: 0.01wt%, ZrO2: 0.015wt%, V2O5: 0.01wt% and 0.14wt% of dioctadecyl dimethyl ammonium chloride according to the mass of the main components. Fe(OH)3, ZnO and MnO were mixed in a ball mill for 3 hours and then dried, and pre-calcined in an air atmosphere at 750°C for 3 hours to obtain a pre-calcined material;

[0061] (2) The pre-sintered material is subjected to secondary crushing using a ball mill, the crushing time is 3 hours, X50 is 0.7 μm, and Co2O3, CaCO3, Nb2O5, V2O5, ZrO2, and dioctadecyl dimethyl ammonium chloride additives are added in the required proportions to obtain a mixed material;

[0062] (3) After the dried mixture is passed through a 60-mesh sieve, 10% PVA is added to granulate the mixture, sieved to remove uneven particles, and pressed into a sample ring blank;

[0063] (4) The sample ring blank is placed in a sintering curve with a sintering temperature between 950° C. and a balanced oxygen partial pressure atmosphere, and is sintered for 7 hours to obtain the manganese-zinc ferrite core.

[0064] Example 3

[0065] The only difference between this embodiment and embodiment 1 is that 0.05 wt % of dioctadecyl dimethyl ammonium chloride is added, and other conditions and parameters are exactly the same as those in embodiment 1.

[0066] Example 4

[0067] The only difference between this embodiment and embodiment 1 is that 0.25 wt % of dioctadecyl dimethyl ammonium chloride is added, and other conditions and parameters are exactly the same as those in embodiment 1.

[0068] Example 5

[0069] The only difference between this embodiment and embodiment 1 is that the auxiliary material composition is Co2O3: 0.35wt%, CaCO3: 0.15wt%, Nb2O5: 0.05wt%, ZrO2: 0.05wt%, V2O5: 0.05wt%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0070] Example 6

[0071] The only difference between this embodiment and embodiment 1 is that the auxiliary material composition is Co2O3: 0.1wt%, CaCO3: 0.01wt%, Nb2O5: 0.01wt%, ZrO2: 0.005wt%, V2O5: 0.005wt%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0072] Comparative Example 1

[0073] The only difference between this comparative example and Example 1 is that Fe2O3 is used as the iron source instead of ferric hydroxide, and the other conditions and parameters are exactly the same as those in Example 1.

[0074] Comparative Example 2

[0075] The only difference between this comparative example and Example 1 is that no dioctadecyl dimethyl ammonium chloride is added, and other conditions and parameters are exactly the same as those in Example 1.

[0076] Comparative Example 3

[0077] The only difference between this comparative example and Example 1 is that dioctadecyl dimethyl ammonium chloride is replaced with polyammonium carboxylate, and the other conditions and parameters are exactly the same as those in Example 1.

[0078] Performance Testing:

[0079] The performance of the magnetic cores obtained in the embodiment and the comparative example was tested, and the test results are shown in Table 1:

[0080] Table 1

[0081]

[0082]

[0083] It can be seen from Table 1 that according to Examples 1-2, the manganese-zinc ferrite core prepared by the method of the present invention can reach a 25°C Bs of more than 544, a 100°C Bs of more than 441, a 25°C Pcv of less than 77, and a 100°C Pcv of less than 120.

[0084] By comparing Example 1 with Examples 3-4, it can be seen that in the preparation process of the manganese-zinc ferrite core of the present invention, the addition amount of dioctadecyl dimethyl ammonium chloride will affect its performance. The addition amount of dioctadecyl dimethyl ammonium chloride is controlled at 0.14-0.18% of the main material weight, and the performance of the manganese-zinc ferrite core obtained is better. If the addition amount of dioctadecyl dimethyl ammonium chloride is too high, if the residual hydrocarbon chains are too much, giant crystals will be generated in the ferrite, causing the overall performance to deteriorate. If the addition amount of dioctadecyl dimethyl ammonium chloride is too low, the residual hydrocarbon chains are small, and the overall performance cannot be significantly improved.

[0085] By comparing Example 1 with Example 5-6, it can be seen that in the preparation process of the manganese-zinc ferrite core of the present invention, the amount of auxiliary materials added will affect its performance. The amount of each auxiliary material added is controlled at Co2O3: 0.2-0.3wt%, CaCO3: 0.08-0.12wt%, Nb2O5: 0.01-0.05wt%, ZrO2: 0.01-0.05wt%, V2O5: 0.01-0.03wt%, and the performance of the manganese-zinc ferrite core is better. The role of Co is to adjust the K1 value of ferrite. Too high and too low Co content causes the overall K1 of ferrite to be far away from 0, causing the hysteresis loss of manganese-zinc ferrite to increase. The role of CaCO3 is to increase the grain boundary resistance of ferrite. If CaCO3 is too low, the grain boundary resistance of ferrite is reduced, the eddy current loss is increased, and too much CaCO3 causes the hysteresis loss to increase. The proper addition of Nb2O5 can refine the grains and increase the grain boundary resistance of ferrite. If Nb2O5 is too low, the grain boundary resistance of ferrite will decrease, the eddy current loss will increase, and if Nb2O5 is too much, the hysteresis loss will increase. The role of ZrO2 is the grain boundary resistance of ferrite. If ZrO2 is too low, the grain boundary resistance of ferrite will decrease, the eddy current loss will increase, and if ZrO2 is too much, the hysteresis loss will increase. The proper addition of V2O5 can improve the Bs of the product. If V2O5 is too low, there will be no obvious effect. If V2O5 is too much, giant crystals will form in the ferrite, resulting in a decrease in the overall performance of the product.

[0086] From the comparison between Example 1 and Comparative Example 1, it can be seen that the present invention uses Fe(OH)3 instead of traditional Fe2O3, which can significantly improve the dispersion uniformity of raw materials and the overall reaction activity of the powder.

[0087] By comparing Example 1 with Comparative Example 2, it can be seen that the present invention adds dioctadecyl dimethyl ammonium chloride in the preparation process of the manganese-zinc ferrite core. Dioctadecyl dimethyl ammonium chloride can play the role of a surfactant due to its hydrophilic group and hydrophobic group. On the other hand, dioctadecyl dimethyl ammonium chloride will promote the densification reaction of manganese-zinc ferrite and increase the density of manganese-zinc ferrite.

[0088] By comparing Example 1 with Comparative Example 3, it can be seen that the dioctadecyl dimethyl ammonium chloride additive of the present invention undergoes three decomposition processes during the subsequent temperature-raising sintering process: in the first stage, a dehydration process occurs at 100°C; in the second stage, a decomposition process to produce hydrogen chloride occurs at 150-200°C; in the third stage, after 200°C, a process of gradual decomposition of hydrocarbon chains occurs. The densification reaction temperature of manganese-zinc ferrite is generally between 600-1000°C. After 600°C, 10% of the hydrocarbon chains of dioctadecyl dimethyl ammonium chloride remain. The residual hydrocarbon chains will act as flux and reducing agent to promote the densification reaction of manganese-zinc ferrite and increase the sintering density of manganese-zinc ferrite. Conventional organic surfactants such as polycarboxylic acid ammonium surfactants have almost no hydrocarbon chains after 600°C and will not play a role in promoting the densification reaction of manganese-zinc ferrite.

[0089] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a manganese-zinc ferrite core, characterized in that: The preparation method comprises the following steps: (1) Fe(OH)3, MnO and ZnO are mixed and pre-sintered to obtain a pre-sintered material; (2) grinding the pre-sintered material, adding auxiliary materials and dioctadecyl dimethyl ammonium chloride additive to obtain a mixed material; (3) granulating the mixed material and pressing it to obtain a blank; (4) Sintering the blank to obtain the manganese-zinc ferrite core.

2. The preparation method according to claim 1, characterized in that The Fe(OH)3 in step (1) is prepared by the following method: Oxygen is introduced into the ferrous salt solution to adjust the pH value to 3-4, and then polyacrylamide flocculant is added. After filtering, oxygen is continued to be introduced into the solution to adjust the pH value to 5-6, and then polyacrylamide flocculant is added. After centrifugation, filtering, washing and drying, the Fe(OH)3 is obtained.

3. The preparation method according to claim 2, characterized in that: The ferrous salt includes ferrous chloride; Preferably, the mass concentration of the polyacrylamide flocculant is 0.8-1.5%; Preferably, the volume of polyacrylamide flocculant added each time is 2 to 3 mL; Preferably, the drying temperature is 100-120°C; Preferably, the drying time is 2 to 4 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The molar ratio of Fe(OH)3, MnO and ZnO in step (1) is (70.1-70.5):(25.1-25.5):(4-4.9); Preferably, the mixing method includes ball milling; Preferably, the ball milling time is 2 to 4 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the pre-sintering treatment in step (1) is 700-800° C. Preferably, the pre-burning treatment time is 2 to 4 hours; Preferably, the atmosphere of the pre-firing treatment comprises air; Preferably, the pre-sintering treatment is followed by ball milling treatment; Preferably, X50 of the pre-sintered material is 0.7-0.8 μm.

6. The preparation method according to any one of claims 1 to 4, characterized in that: The auxiliary materials in step (2) include Co2O3, CaCO3, Nb2O5, ZrO2 and V2O5; Preferably, based on the total mass of the Fe(OH)3, MnO and ZnO being 100%, the mass of the Co2O3 is 0.2-0.3%; Preferably, the mass of CaCO3 is 0.08-0.12%; Preferably, the mass of Nb2O5 is 0.01-0.05%; Preferably, the mass of ZrO2 is 0.01-0.05%; Preferably, the mass of the V2O5 is 0.01-0.03%.

7. The preparation method according to any one of claims 1 to 6, characterized in that: Based on the total mass of Fe(OH)3, MnO and ZnO being 100%, the mass of the dioctadecyl dimethyl ammonium chloride additive is 0.14-0.18%.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The step (3) of screening before granulation; Preferably, the mesh size of the sieve is 50 to 80 meshes; Preferably, the granulation process comprises mixing the mixed material with a 10% polyvinyl alcohol solution for granulation.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The sintering temperature in step (4) is 900-1000° C. Preferably, the sintering treatment time is 6 to 8 hours; Preferably, the sintering process is performed according to a sintering curve of a balanced oxygen partial pressure atmosphere.

10. A manganese-zinc ferrite core, characterized in that: The manganese-zinc ferrite core is obtained by the method as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Manganese zinc ferrite magnetic core and preparation method thereof

    CN113072370A

  • Preparation method of iron source for manganese zinc ferrite

    CN113582238A